Analisis Keterampilan Mahasiswa sebagai Pemimpin Kelompok daam Kegiatan Praktikum Fisika - Irnin Agustina Dwi Astuti; Prahesti Tirta Safitri; Lodya Sesriyani; M Japar; Moch Sukardjo (Universitas Indraprasta PGRI Jakarta, 2023)
Leaders in a group have an important role to organize their members so that the goals of the group can be achieved. The ability of the leader in the basic physics practicum group is in fact not working effectively, therefore it is necessary to analyze the basic abilities that a leader must have. The purpose of this study is to analyze the skills of students as a leader of the basic physics practicum group. This research is a qualitative research with research instruments in the form of observation sheets and questionnaire sheets. Based on the results and discussion, it can be concluded that the basic skills of a leader in the basic physics practicum group were obtained on average by 8.9 with a moderate category. These basic skills are based on the leader's indicators, namely analytical ability, communication skills, courage, listening ability, assertiveness, and the ability to provide encouragement. With these basic skills, a leader in the basic physics practicum group is able to organize its members in participating in practicum activities in accordance with existing procedures.